Hubungan Waktu Tunggu Terhadap Kepuasan dalam Pelayanan Kesehatan di Puskesmas Aek Batu - Dinda Sri Kesuma; Susilawati Susilawati Susilawati (Syntax Idea, 2022)
Health services are efforts to maintain health, improve and treat disease in individuals/groups of the wider community. In getting health services, you must follow the procedure first, which must follow the waiting time. Waiting time is the initial image of service. The waiting time used by patients to get health services starting from the place of registration, examination, taking drugs until completion and leaving health services. During the waiting time process, handling is needed so that the community does not have suggestions that the puskesmas service is very bad or it can be said that they do not follow the existing procedures. Inefficient waiting times lead to patient dissatisfaction. The main factors and benchmarks for the success of puskesmas services have an impact on the number of visits, satisfied patients tend to return. This study aims to see the relationship between registration time to completion in order to provide services as expected by the community.